Synthesis, Secondary Structure, and Anion Binding of Acyclic Carbohydrate-Derived Oligo(amide-triazole)s - Fidalgo, Daniela Marina (2018)
A family of linear, carbohydrate-derived oligo(amide-triazole)s has been designed and synthesized. These molecules possess a regular distribution of triazole rings (from one to four) linking the carbohydrate units to give dimer to pentamer derivatives. Their binding to halide anions was qualitatively analyzed by means of NMR spectroscopy and mass spectrometry. All the compounds were able to bind chloride anions, with a stoichiometry that depended on the chain length. The dimer and trimer gave 2:1 host/chloride ratio, while the tetramer and pentamer gave 1:1 complexes. The secondary structure of the oligo(amide-triazole)s was studied using NMR spectroscopy and circular dichroism. These studies showed that the larger host molecules (tetramer and pentamer) adopted a stabilized U-turn and were able to bind just one chloride anion. Only the pentamer displayed a helical conformation, which was slightly distorted in the presence of chloride salts. Interestingly, chloride binding involves not only the triazole-CH but also H atoms from the carbohydrate moieties. These compounds could be applied for chloride sensing by ESI-MS.